Memory Performance with Intractable Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
The cognitive and psychological predictors of everyday memory were investigated in 37 children (mean age 13.7 years, range 7.3-17.9 years) with medically intractable epilepsy treated at the Hospital for Sick Children, Toronto, Canada.